THE IMPACT OF ACCOUNTING INFORMATION SYSTEMS AS A CONTROL AND AUDIT TOOL ON FAIR VALUE ACCOUNTING APPLICATIONS: A STUDY ON COMPANIES LISTED ON THE IRAQ STOCK EXCHANGE - Emad Al-Harash (Journals Park Publishing, 2024)
The study looks at how the accounting information system affects the connection between using fair value accounting and the qualities of accounting information that the system creates and shows in the financial statements of Iraqi Stock Exchange companies. These qualities are relevance, faithful representation, and comparability. The results make it clear how important IFRS 9 and the accounting information system are for making financial reporting more useful.
Keywords: accounting information systems, fair value, accounting applications, Control, Audit and Iraq Stock Exchange.